Iodine and hypothyroidism in neonates with congenital heart disease. Issue 3 (1st November 1997) - Linder, N; Sela, B; German, B; Davidovitch, N; Kuint, J; Hegesh, J; Lubin, D; Sack, J
Abstract : AIM: To evaluate the influence of the intravenous injection of iodine during cardiac catheterisation, and of topical iodine antiseptics during surgical procedures, on thyroid function in full term neonates. METHODS: Twenty one full term infants with major cardiac anomalies who survived for more than a month were studied. Thyroxine and thyrotropin concentrations were measured (by radioimmunoassay) before each procedure, 24 hours after the procedure, and every week thereafter until the age of 1 month or until normal. Thyroxine values less than 64.4 nmol/l were considered low, while thyrotropin values greater than 30 mU/l were considered high. RESULTS: Thyroid function tests before iodine exposure were within normal limits in all infants. Following catheterisation or surgery six infants had raised thyrotropin concentrations; three had low thyroxine concentrations. Two of those infants were treated with L-thyroxine. CONCLUSION: Iodine exposure during cardiac catheterisation or surgery may induce transient hypothyroidism in term infants.